2020
DOI: 10.1038/s41524-020-00408-1
|View full text |Cite
|
Sign up to set email alerts
|

Topological pruning enables ultra-low Rayleigh scattering in pressure-quenched silica glass

Abstract: Silica glass is the most indispensable material in optical communication applications due to its superior optical properties. The transmission loss of silica glass has been reduced over the past 30 years by continuous efforts toward decreasing density fluctuations by lowering of fictive temperature, e.g., through improvements in processing or doping. A recent study has shown that shrinkage of structural voids by hot compression is a promising way to further decrease the loss. However, an atomic understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…Using the FMP‐v2, density fluctuations of F‐doped AS glasses were evaluated to estimate the effect of the co‐doping on the Rayleigh scattering of silica glass since Rayleigh scattering is known to be related to the density and concentration fluctuations of materials in the nanoscale 51,52 . Note that density fluctuations normalized by density (ρ), σρ/ρ, were compared to eliminate the effect of density change by the additives 53,54 . As noted in the Computational Method section, relatively large models composed of more than 50,000 atoms were used and five independent replicas were examined to evaluate the average and deviation of the normalized density fluctuations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the FMP‐v2, density fluctuations of F‐doped AS glasses were evaluated to estimate the effect of the co‐doping on the Rayleigh scattering of silica glass since Rayleigh scattering is known to be related to the density and concentration fluctuations of materials in the nanoscale 51,52 . Note that density fluctuations normalized by density (ρ), σρ/ρ, were compared to eliminate the effect of density change by the additives 53,54 . As noted in the Computational Method section, relatively large models composed of more than 50,000 atoms were used and five independent replicas were examined to evaluate the average and deviation of the normalized density fluctuations.…”
Section: Resultsmentioning
confidence: 99%
“…51,52 Note that density fluctuations normalized by density ( ), ∕ , were compared to eliminate the effect of density change by the additives. 53,54 As noted in the Computational Method section, relatively large models composed of more than 50,000 atoms were used and five independent replicas were examined to evaluate the average and deviation of the normalized density fluctuations. First, alumina was added to the SiO 2 -F1 model, which contains approximately 1.25 wt% fluorine, to understand the effect of alumina, as shown in Figure 11(A).…”
Section: Effect Of Alumina Co-doping Into Fdoped Silica Glassmentioning
confidence: 99%
“…Alternatively, atomistic simulations are capable of easily outputting various metrics to characterize the medium‐range structure even though it might fall short of precisely reproducing the real glass structure. Insights obtained from simulations with respect to medium‐range structure characterization on many glass systems have proven to be useful and constructive as demonstrated by many studies 10,12,20‐24 …”
Section: Introductionmentioning
confidence: 99%
“…Insights obtained from simulations with respect to medium-range structure characterization on many glass systems have proven to be useful and constructive as demonstrated by many studies. 10,12,[20][21][22][23][24] Besides composition, temperature and pressure are two additional effective avenues to control glass structure and tailor glass properties. For instance, Guerette et al 25 has shown that high temperature (1100°C) and pressure (up to 8 GPa) could result in a density increase of ~25% and Young's modulus increase of ~71% for silica glass.…”
mentioning
confidence: 99%
“…For example, Masuno et al 7 have found that both a higher refractive index and a higher Abbe number, comparable to α ‐quartz, can be achieved via high‐temperature densification of the glass at a pressure of 7.7 GPa. Results from experiments 8 and atomic‐scale simulations 9 have shown that the density fluctuations and optical loss of silica glass can be significantly suppressed using an appropriate pressure‐quench process. In addition, experimental results have shown that hot‐compressed silica glass has a higher thermal stability than cold‐compressed silica glass 10,11 .…”
Section: Introductionmentioning
confidence: 99%